Pelatihan Penyusunan Rencana Pelaksanaan Pembelajaran (RPP) Berdiferensiasi pada Guru Madrasah Ibtidayah - Andi Saddia; Nur Aisyah Humairah; Aulia Rahmadhani; Faizal Amir (Universitas Pahlawan Tuanku Tambusai, 2023)
Theoretical studies and empirical studies show that Differentiated Learning is effective in supporting the diverse needs of students in learning. However, only a few teachers can develop differentiated learning plans. Teachers in the Madrasah Ibtidaiyah Working Group (KKMI) in Mapilli District, Polewali Mandar Regency, West Sulawesi still need training and assistance in preparing Lesson Plans (RPP) according to the Differentiated Learning Concept. Therefore, this service activity aims to facilitate teachers at the KKMI in making lesson plans according to the concept of Differentiated Learning. This activity was carried out in the form of workshops and training as well as mentoring in preparing lesson plans, with a total of 21 teachers participating. The methods used are the method of lectures, discussions, questions and answers, and practice. The achievements in implementing this training and mentoring are increasing the knowledge and ability of teachers to prepare lesson plans according to the concept of Differentiated Learning.